Optimization Extraction of Sunflower Seed Oil (Helianthus Annus) Using Factorial Design Experiment with Soxhlation Method - Shabrina, Shabrina; Broto, R. T. D. Wisnu (Vocational College of Universitas Diponegoro, 2023)
Sunflower seed oil is one type of vegetable oil whose growth is still in its early stages in Indonesia. Due to a shortage of domestic availability, several edible oil enterprises in Indonesia still need to import a significant amount of sunflower seed oil. Rukmana (2004) states that the content of sunflower oil's content ranges from 23 to 45%. 11.7% oleic acid and 44-72% linoleic acid are both present in sunflower oil. The goal of this study was to identify the best process factors in light of the obtained oil yield. This study's used Fractional Design Experiment 23 with Quicker Method analysis. The results showed that the optimal operating conditions were an extraction time of 185 min, temperature of 60 ℃, and material-solvent ratio of (R) of 1:6, yielding an oil of 51.6%.